A computer integrated manufacturing system for low repetitive and high product-mix components - Ginting A.,; Che Hassan Che Haron, (2004)
This paper describes a strategy to fulfill the needs of the 21st century metalworking industry, especially for the industry that produces the low repetitive and high productmix components using machining centres. The approach of strategy is emphasized in developing of computer integrated manufacturing (CIM) software technology. The designed software comprises of computer aided design (CAD) and computer aided manufacturing (CAM) modules, which is supported by common and working databases, run through dialogue box as the primary user interface inside AutoCAD', and written in ARK (AutOCAD' Runtime eXtension, the C++ Application Programming lnterface to AutoCAD'). The CAD module provides user with capabilities of designing product model by feature~based design and obtaining product data. The product model is displayed on screen in AutoCAD' environment, while the product data is maintained by the Database Management System (DBMS). before transferring it downstream to CAM module. The Structured Query Language (SQL) is used to link the CAM module to DBMS to provide a two-way flow data. Finally, the product data is entered to CAM module for process planning purposes, which is supported by machine tool and fixture databases. The ultimate goal of the software is to solve the CAD, computer aided process planning (CAPP), CAM integration and operation planning that consists of machining data generation and tool selection from the tool database, and NC program generation